MEDIA STRATEGY IN UPHOLDING THE TRUTH IN POST TRUTH ERA - Taufik, Cevi Mochamad; Suryana, Nana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Initially the mass media acted as the sole interpreter of truth, but now it is divided into many versions of truth. The treatise of truth presented is distorted by the truths of media construction on the internet network. Truth is no longer valuable and becomes relative. This condition made people confused, believing the truth from the media soon disappeared because it was annulled by other media. However, the public cannot be separated from their dependence on information and always seek and apply themselves to the media. Based on this description, the research is directed to uncover the phenomenon of truth in the post-truth era by using qualitative methods that emphasize mainstream media strategies in spreading, shaping, and confirming public beliefs. The results of the study show that the strategy of upholding the truth is part of daily activities by penetrating online networks carried out by all subsidiaries by spreading the truth based on the ethical principles contained in the Journalistic Code of Ethics and the Basic Press Law, as well as value principles that refer to facts, objectivity. , as well as verification, as a guide to the value of information by educating the public about the types of verified information, conducting campaigns regarding media credibility, to efforts to support the movement to fight hoax.